The Effectiveness of Online Petitions About Environmental Issues on The Change.org Site Users - Widiastiana Vista Wijaya; Edy Prihantoro; Sugiharti Binastuti (Department of Communications, Universitas Islam Indonesia, 2019)
Environmental problems are issues vital to human life and other living creatures. Through the development of technology and information, the public can be engaged in massive street protests against the parties who should be responsible for damage to the environment and environmental protection campaign. During 2018, environmental issues became popular topic at the online petition on the Change.org website. “Seruan Penetapan Hari Hutan Indonesia” is a themed online petition environmental issues that have the support of more than 538 thousand signatures. This study was conducted to determine the effectiveness of an online petition on Change.org environmental issues at the site using a measurement EPIC (Empathy, Persuasion, Impact, Communication) Model. The quantitative research approach to use the paradigm of positivism. Methods of data collection are done through questionnaires to 100 followers Instagram account Change.org. The results showed that the online petition on environmental issues is the first dimension of empathy, of the affection and cognition, the saturation level that online petitions on environmental issues can be accepted by users. Secondly, persuasion dimension, related to changes in confidence and the desire to behave, familiarize yourself that users have the perception that online petitions on environmental issues right on the website Change.org. Third, the impact dimension, namely knowledge and involvement of the message effective, though users do not always share information petition to social media or instant messaging applications. Fourth, the dimensions of communication, messages and the user's understanding of environmental issues online petition which was signed on the website Change.org. Based on the results of the study prove that the theory of S-O-R (Stimulus-Organism-Response), namely the higher the level of attention on stimulus in the form of empathy and persuasion of the message delivered, the more effective the impact and communication carried out by Change.org Instagram active users.